Synthesis of Palmitate Curcumin Ester via Steglich Esterification and Evaluation of Antimicrobial Activity and Toxicity against Daphnia magna - Mentari Zikri Anty (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
Curcumin possesses a wide range of biological activities; however, its practical application is constrained by poor aqueous solubility and low bioavailability. Chemical modification via esterification with fatty acids offers a promising strategy to enhance its physicochemical properties and biological performance. This study aimed to synthesize palmitate curcumin esters through Steglich esterification and to evaluate their antimicrobial activity as well as their toxicity toward Daphnia magna. The synthesis was performed by reacting curcumin with palmitic acid in the presence of N, N-dicyclohexylcarbodiimide (DCC) and 4 dimethylaminopyridine (DMAP) as coupling agents. The resulting mono- and dipalmitate curcumin esters were subsequently purified using column chromatography and characterized by Fourier Transform Infrared (FT-IR) and UV–Visible spectroscopy to confirm the successful formation of ester bonds. Antimicrobial activity was assessed against Staphylococcus aureus and Escherichia coli using the disk diffusion method, while acute toxicity was evaluated using Daphnia magna through LC₅₀ determination. The findings revealed that both ester derivatives exhibited relatively weak antimicrobial activity, with inhibition zones ranging from 7.00 to 8.33 mm. In contrast, toxicity evaluation demonstrated that monopalmitate–curcumin exhibited higher toxicity (LC₅₀ = 153.65 mg/L) compared to dipalmitate–curcumin (LC₅₀ = 412.28 mg/L). This difference is likely attributed to the presence of a free phenolic hydroxyl group in the monoester structure, which may enhance its biological reactivity. Overall, the results suggest that esterification modifies curcumin’s properties, although further optimization is required to improve its antimicrobial efficacy while maintaining acceptable toxicity levels.